Oral lipoic acid as a treatment for acute optic neuritis: a blinded, placebo controlled randomized trial. Issue 2 (May 2019) - Falardeau, Julie; Fryman, Allison; Wanchu, Rohan; Marracci, Gail H; Mass, Michele; Wooliscroft, Lindsey; Bourdette, Dennis N; Murchison, Charles F; Hills, William L; Yadav, Vijayshree
Background: Lipoic acid, an antioxidant, has beneficial effects in experimental acute optic neuritis and autoimmune encephalomyelitis. Optical coherence tomography can detect retinal nerve fiber layer thinning, representing axonal degeneration, approximately 3–6 months after acute optic neuritis. Objective: To determine whether lipoic acid is neuroprotective in acute optic neuritis. Methods: A single-center, double-blind, randomized, placebo controlled, 24-week trial. Intervention included 6 weeks of once daily lipoic acid (1200 mg) or placebo within 14 days of acute optic neuritis diagnosis. The primary outcome was the mean difference in affected eye retinal nerve fiber layer (RNFL) thickness from baseline to 24 weeks. Results: We enrolled 31 subjects (placebo n=16; lipoic acid n=15; average age 38.6 years (standard deviation (SD) 10.3)). Affected eye mean global RNFL thickness (µm) in the lipoic acid group decreased from 108.47 (SD 26.11) at baseline to 79.31 (SD 19.26) at 24 weeks. The affected eye RNFL in the placebo group decreased from 103.67 (SD 18.04) at baseline to 84.43 (SD 20.94) at 24 weeks. Unaffected eye RNFL thickness did not significantly change in either group over 24 weeks. Conclusion: Six weeks of oral lipoic acid supplementation after acute optic neuritis is safe and well tolerated; however, because of insufficient recruitment, we could not conclude that lipoic acid treatment was neuroprotective in acute optic neuritis.